Vehicle Sticker System using Blockchain Technology for UTHM - Lee, Kin Wai; Harun, Nur Ziadah (Applied Information Technology And Computer Science, 2024)
In the era of globalization, blockchain technology offers transformative benefits, including improved security, transparency, and efficiency. Traditional vehicle sticker systems face issues like counterfeiting, inefficiency, and vulnerability to security breaches due to their reliance on centralized databases. This project investigates integrating blockchain into a Vehicle Sticker System to enhance security and streamline processes. The proposed system uses blockchain’s immutable ledger and smart contracts to ensure sticker authenticity, prevent fraud, and automate issuance and verification. Targeted at UTHM users, this user-friendly web platform aims to provide seamless sticker management, contributing valuable insights into blockchain’s application in university administration.